2018
DOI: 10.1007/s11144-018-1383-3
|View full text |Cite
|
Sign up to set email alerts
|

CO oxidation over Pt/SnO2 catalysts

Abstract: The influence of treatment conditions on Pt/SnO 2 properties and its catalytic activity in CO oxidation was investigated. It was found that the temperature and atmosphere of catalyst heating had a great impact on the active phase dispersion, the chemical composition of the surface layer and the O 2 adsorption capacity of the Pt/SnO 2 catalysts. TOF-SIMS analysis and XRD measurements showed that the heat treatment in an atmosphere of H 2 promotes the formation of bimetallic compounds of Pt-Sn and different spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Figure 10 shows H2-TPR results. SN samples are relatively easily reduced with H2 according to the simplified equation SnO2 + 2 H2 → Sn + 2 H2O [19,20]. The H2-TPR curve of the pristine α-SnO2 (sample SN-0) showed that the reduction of SnO2 started at about 180 °C and ended with an "incomplete" maximum at 643 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 shows H2-TPR results. SN samples are relatively easily reduced with H2 according to the simplified equation SnO2 + 2 H2 → Sn + 2 H2O [19,20]. The H2-TPR curve of the pristine α-SnO2 (sample SN-0) showed that the reduction of SnO2 started at about 180 °C and ended with an "incomplete" maximum at 643 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Figure10shows H 2 -TPR results. SN samples are relatively easily reduced with H 2 according to the simplified equation SnO 2 + 2 H 2 → Sn + 2 H 2 O[19,20]. The H 2 -TPR curve of the pristine α-SnO 2 (sample SN-0) showed that the reduction of SnO 2 started at about 180 • C and ended with an "incomplete" maximum at 643 • C. The incomplete reduction of SnO 2 to Sn can be attributed to the formation of the SnO and/or Sn metal shell around the α-SnO 2 particles.…”
mentioning
confidence: 99%
“…Bond et al demonstrated the superior activity of Pd/SnO 2 compared with Pd/SiO 2 and Pd/Al 2 O 3 , which was attributed to the spillover of CO and O 2 from the metal to the support [21]. The high activity of Pd/SnO 2 and Pt/SnO 2 catalysts have also been reported by numerous authors [21][22][23][24][25][26][27], with several mechanisms proposed to account for the enhanced catalytic activity. Sheintuch et al also suggested a spillover mechanism, although it was considered to be restricted to CO [24].…”
Section: Introductionmentioning
confidence: 83%
“…In particular, two-dimensional (2D) crystals with large lateral dimensions are ideal model systems, and hence understanding and controlling their crystal growth is critical . Oxides of earth-abundant tin have found widespread applications in different fields such as gas sensing, solar cells, catalyst supports, batteries, and transparent electronics . Thermodynamically stable rutile Sn­(IV) oxide SnO 2 (cassiterite) is commonly used for all of these applications.…”
Section: Introductionmentioning
confidence: 99%